Infrarenal aortic clamp reviving a patient from acute surgical haemorrhagic shock: a novel management technique. (19th October 2016) - Kumar, Ranjith; Satya Prakash, M V S; Das, Subhasree; Manikandan, Ramanitharan
Abstract : Surgical management of renal cell carcinoma extending into the inferior vena cava (IVC) is almost always accompanied by massive intraoperative blood loss and associated complications. It is a widely recognised problem, and its active management is essential in improving the perioperative morbidity and mortality. We share our experience with a similar case of open radical nephrectomy with massive blood loss of twice the circulating volume in a duration of <8 surgical hours. Although we emphasise the goals of securing haemostasis, restoration of circulating volume, and efficient management by replacing blood components, in the present case, despite the above-mentioned goals being fulfilled, we were unable to extricate the patient from haemorrhagic shock by conventional means and therefore resorted to desperate measures, namely the novel approach of infrarenal aortic clamping along with higher than recommended vasopressor support. We resorted to this in order to maintain the haemodynamic parameters and to prevent avoidable morbidity and mortality related to persistent intraoperative hypotension. With such an approach, we successfully managed the patient perioperatively, ultimately resulting in the patient being discharged after a week of intensive care unit stay without major complications.